Relações enunciativas no percurso da aquisição da escrita das palavras: o caso das convenções ortográficas - Laimer, Juliana (2024)
The research theme of this research involves the enunciative relationships that mark the path of acquiring written words, with emphasis on the case of orthographic conventions, based on the theoretical-methodological device (I-you/he)-HE. The general objective is to reflect on the role of enunciative relations in the appropriation of spelling conventions by a group of writing children, in light of the theoretical-methodological device (I-you/he)-HE. To develop the chosen theme and achieve the objective, a path was taken. Chapter two focuses on the studies of Teberoski, Ferreiro and the contributions of Morais, addressing the developmental perspective on language acquisition. This chapter presents how language acquisition occurs, exploring the cognitive development of learning the mother tongue. Furthermore, it is in chapter three that we enter into the enunciative perspective proposed in the topic of this research. The chapter seeks to explore language acquisition from Benvenistian texts, exploring concepts such as language, language, enunciation and the relationship between semantics and semiotics. We will also find reflections, in order to understand the movements and displacements that the child makes to represent the language in an image: the appropriation of written language. To this end, the relationships of subjectivity and intersubjectivity between the speaker/listener and the writer/reader stand out. The contributions of Silva (2009) are also present in this research. His approach to enunciative operations contributes to the understanding of the movements carried out by the I-you in the child's introduction to language. The text deals with the complexity of written language and the importance of you (listening) so that spoken language can be converted into written language. The role of you in helping the child graphically represent the language is fundamental in approaching a reflection regarding the correct writing of words. Enunciative relationships promote the child's introduction to written language, as writing is not a direct manifestation like speech, writing requires from the writer the need to convert speech into writing, and cultural manifestations take place in the complexity of relationships (I -you/he) -HE. Finally, to account for the development of the chosen theme, we carried out analyzes of enunciative excerpts promoted from language practices, planned and carried out with children living in the Planaltina neighborhood of Passo Fundo. It was in these excerpts that we found the importance of enunciative relationships in the process of acquiring written words to understand how children appropriate spelling conventions. Therefore, the research highlights that it is in the enunciative act and only in it that we find the relationships between the I-you, it is in this movement that we reveal the subjects in the culture of the language, in this way, before the appropriation of orthographic norms, children experience the language through enunciation and then understand that the correct writing of words is part of the language system.